Ultrasound combined with targeted cationic microbubble-mediated angiogenesis gene transfection improves ischemic heart function - Zhou, Qing (Exp Ther Med, 2017)
The present study aimed to construct targeted cationic microbubbles (TCMBs) by synthesizing cationic microbubbles conjugated to an intercellular adhesion molecule-1 (ICAM-1) antibody, and then to use the TCMBs to deliver the angiopoietin-1 (Ang-1) gene into infarcted heart tissue using ultrasound-mediated microbubble destruction. It was hypothesized that the TCMBs would accumulate in higher numbers than non-targeted cationic microbubbles (CMBs) in the infarcted heart, and would therefore increase the efficiency of targeted Ang-1 gene transfection and promote angiogenesis. The results of the study demonstrated that the ability of TCMBs to target inflammatory endothelial cells was 18.4-fold higher than that of the CMBs in vitro. The accumulation of TCMBs was greater than that of CMBs in TNF-α-stimulated human umbilical cord veins, indicated by a 212% higher acoustic intensity. In vivo, the TCMBs specifically accumulated in the myocardial infarct area in a rabbit model. Three days after ultrasound microbubble-mediated gene transfection, Ang-1 protein expression in the TCMB group was 2.7-fold higher than that of the CMB group. Angiogenesis, the thickness of the infarct region and the heart function of the TCMB group were all significantly improved compared with those in the CMB and control groups at 4 weeks following gene transfection (all P<0.01). Therefore, the results of the current study demonstrate that ultrasound-mediated TCMB destruction effectively delivered the Ang-1 gene to the infarcted myocardium, resulting in improved cardiac morphology and function in the animal model. Ultrasound-mediated TCMB destruction is a promising strategy for improving gene therapy in the future.